A Push–Pull PdII Complex with a Ternary Pd–P–C+ Accepting End and a Key N‐Heterocyclic Carbene–Imidazoliophosphine Ligand (Eur. J. Inorg. Chem. 3/2016). Issue 3 (21st January 2016) - Dubrulle, Laurent; Poidevin, Corentin; Maaliki, Carine; Canac, Yves; Lepetit, Christine; Duhayon, Carine; Chauvin, Remi
Abstract : The cover picture shows the quasi‐isostructural polarization of a neutral Pd II complex, where a highly donating imidazol‐2‐ylidene C‐ligand faces an electron‐poor imidazo lo phosphine P‐counterpart undergoing a dramatic enhancement of its local electron deficiency by chemical ionization with CH3 + . Upon optical excitation at low energy, the accepting character of the resulting imidazo lio phosphine moiety competes with the intrinsic electronegativity of the PdCl2 center. At higher energy, however, UV light promotes depolarization through a clear‐cut hole–electron dissociation with a residual overlap at the Pd center. In a marine scenery, this three‐step phenomenon is viewed as a rise in electronic energy from the realm of ground‐state chemistry under the sea level, where UV light is absorbed, to the sun‐drenched heaven of excited states, through the surface of gleaming waters where the electron–hole pair start to appear around the metal center. Details are discussed in the article by R. Chauvin et al. onp. 313 ff . For more on the story behind the cover research, see theCover Profile .